Process development and simulation of a novel solar energy plant integrated with solid oxide fuel cell, hydrogen, heat recovery and carbon capture systems - Muhammad Ishaq; Ibrahim Dincer (International Journal of Thermofluids)
Solid oxide fuel cell (SOFC) releases significant high-temperature thermal energy during its operational mode. If this heat is not managed properly, it leads to thermal stresses, material shocks, and degradation. To effectively utilize such a high-temperature heat, this work presents a thermodynamic analysis and environmental assessment of a novel concept that synergistically integrates a benchmark SOFC with a four-step hybrid Cu-Cl thermochemical cycle. The developed system incorporates a SOFC unit for electricity generation, an afterburner for the complete oxidation of unreacted fuel (H2, CO), a thermochemical cycle for utilizing high-temperature heat, a supporting Rankine Cycle (SRC), and an H2 and CO2 compression unit. The system is simulated by solving mass, energy, and exergy balances at steady-state conditions. Pinch point analysis is conducted using MATLAB to assess the thermodynamic feasibility of H2 production. Furthermore, the specific primary energy consumption per unit of CO2 avoided (SPECCA) is calculated to assess the system's environmental impacts. It is found that the CO2 and H2 compression train exhibit an overall exergy destruction of 5.83 kJ/mol of CO2 and 5.98 kJ/mol of H2 respectively. The thermolysis reactor of the Cu-Cl cycle carries the highest exergetic losses, with a share of 34.39%. The system exhibits a SPECCA value of 8.27 with 0.114 MJ/kg CO2, considering the options with and without the Cu-Cl thermochemical cycle. The system's overall energy and exergy efficiencies are also 64.45% and 59.07% respectively.